Improving The Methodological Issues Of Accounting For Human Capital Investments (Progress Annals: Journal of Progressive Research, 2024)
The article examines the economic content of human capital and investments in it and its interpretation as an object of accounting. Suggestions were made for the recognition, classification and reflection of investments in human capital as an object of accounting and an element of financial reporting in business entities, and the author's definitions of the concept of investment in human capital, human capital were given.